Pelatihan Media Pembelajaran Interaktif Berbasis Game Edukasi Kahoot Di SMP Pada Materi Bilangan Bulat - Dewi Anggreini; Sukiyanto Sukiyanto; Denik Agustito (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
Enjoyable learning can influence student learning outcomes. Learning success is influenced by several factors, one of which is the learning media factor. Technology-based learning media is very likely to overcome problems that often arise in the world of learning. Because technology has a very important role in developing innovation, ideas or concepts in learning. With technology, learning can be packaged into games, one of which is the Kahoort educational game. The priority problems faced by junior high schools are: (1) Weak student understanding of negative integers (-). The solution to overcome this problem is: Improving student understanding by using Kahoort educational game-based learning media; (2) Teachers need innovation in learning. The solution to overcome this problem is: Introducing students to interactive learning media based on Kahoort educational games. The implementation of this community service uses a training method, using quantitative. The community service instrument uses a questionnaire. The results obtained are that this community service received high enthusiasm from community service participants (training) and partners where the community service was held.